Impact of Policy of Soybean Price Stability on Imported and Local Soybean Price - Muhammad Adi Sofyan Ansori; Deky Aji Suseno (Economics Development Analysis Journal, 2017)
The research aims at analyzing the impact of PKSHK (Duty, Import Income Tax, and Subsidy) and the Imported Soybean Price on the Local Soybean Price. This research is a quantitative research, the data used in this research is time series secondary data starting from January 2005 to December 2014. The method of analysis is Multiple Linear Regression and Simple Linear Regression. The tests used are statistical t-test and F-test statistics. The results of this research show that the variables of PKSHK do not significantly have impact on the Local Soybean Price, while the variable of Soybean Import Price positively and significantly has impact on the Local Soybean Price. The conclusion of this research is that PKSHK made by the government is not effective.